Effect of sub-chronic exposure to cigarette smoke, electronic cigarette and waterpipe on human lung epithelial barrier function - AKGÜN ÖLMEZ, SEVCAN GÜL (BMC, 2020)
BackgroundTaking into consideration a recent surge of a lung injury condition associated with electronic cigarette use, we devised an in vitro model of sub-chronic exposure of human bronchial epithelial cells (HBECs) in air-liquid interface, to determine deterioration of epithelial cell barrier from sub-chronic exposure to cigarette smoke (CS), e-cigarette aerosol (EC), and tobacco waterpipe exposures (TW).MethodsProducts analyzed include commercially available e-liquid, with 0% or 1.2% concentration of nicotine, tobacco blend (shisha), and reference-grade cigarette (3R4F). In one set of experiments, HBECs were exposed to EC (0 and 1.2%), CS or control air for 10days using 1 cigarette/day. In the second set of experiments, exposure of pseudostratified primary epithelial tissue to TW or control air exposure was performed 1-h/day, every other day, until 3 exposures were performed. After 16-18h of last exposure, we investigated barrier function/structural integrity of the epithelial monolayer with fluorescein isothiocyanate-dextran flux assay (FITC-Dextran), measurements of trans-electrical epithelial resistance (TEER), assessment of the percentage of moving cilia, cilia beat frequency (CBF), cell motion, and quantification of E-cadherin gene expression by reverse-transcription quantitative polymerase chain reaction (RT-qPCR).ResultsWhen compared to air control, CS increased fluorescence (FITC-Dextran assay) by 5.6 times, whereby CS and EC (1.2%) reduced TEER to 49 and 60% respectively. CS and EC (1.2%) exposure reduced CBF to 62 and 59%, and cilia moving to 47 and 52%, respectively, when compared to control air. CS and EC (1.2%) increased cell velocity compared to air control by 2.5 and 2.6 times, respectively. The expression of E-cadherin reduced to 39% of control air levels by CS exposure shows an insight into a plausible molecular mechanism. Altogether, EC (0%) and TW exposures resulted in more moderate decreases in epithelial integrity, while EC (1.2%) substantially decreased airway epithelial barrier function comparable with CS exposure.ConclusionsThe results support a toxic effect of sub-chronic exposure to EC (1.2%) as evident by disruption of the bronchial epithelial cell barrier integrity, whereas further research is needed to address the molecular mechanism of this observation as well as TW and EC (0%) toxicity in chronic exposures.
Keywords: E-cigarette; Cigarette; Nicotine; E-cadherin; Waterpipe; Tobacco; Cilia; AIR-LIQUID INTERFACE; MESENCHYMAL TRANSITION; MUCOCILIARY CLEARANCE; CELLS; DYSFUNCTION; NICOTINE; INFLAMMATION; EXPRESSION; MODEL; GENE